2008
DOI: 10.1128/aac.01033-07
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antimalarial Activity and Heme Alkylation for Spiro- and Dispiro-1,2,4-Trioxolane Antimalarials

Abstract: The reaction of spiro-and dispiro-1,2,4-trioxolane antimalarials with heme has been investigated to provide further insight into the mechanism of action for this important class of antimalarials. A series of trioxolanes with various antimalarial potencies was found to be unreactive in the presence of Fe(III) hemin, but all were rapidly degraded by reduced Fe(II) heme. The major reaction product from the heme-mediated degradation of biologically active trioxolanes was an alkylated heme adduct resulting from add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
111
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 33 publications
11
111
0
Order By: Relevance
“…We measured the efficiency of heme alkylation for these trioxolanes, trioxanes and trioxepanes using these same experimental conditions. 30 Significant heme alkylation was observed within 30 s for the active 1c (67 ± 2%) and moderately active 2b (55 ± 4%), and to a slightly lesser extent for the less active 1b (50 ± 1%) and 2a (45 ± 1%); however the extent of heme alkylation by these compounds was far lower than previously reported for the highly active trioxolanes 1a (86 ± 0.2%) and OZ277 (83 ± 2%). 30 Trioxepanes 3a and 3b mediated very little heme alkylation (25 ± 1% and 1 ± 0.4%), in agreement with their lack of antimalarial activity.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…We measured the efficiency of heme alkylation for these trioxolanes, trioxanes and trioxepanes using these same experimental conditions. 30 Significant heme alkylation was observed within 30 s for the active 1c (67 ± 2%) and moderately active 2b (55 ± 4%), and to a slightly lesser extent for the less active 1b (50 ± 1%) and 2a (45 ± 1%); however the extent of heme alkylation by these compounds was far lower than previously reported for the highly active trioxolanes 1a (86 ± 0.2%) and OZ277 (83 ± 2%). 30 Trioxepanes 3a and 3b mediated very little heme alkylation (25 ± 1% and 1 ± 0.4%), in agreement with their lack of antimalarial activity.…”
mentioning
confidence: 64%
“…30 Significant heme alkylation was observed within 30 s for the active 1c (67 ± 2%) and moderately active 2b (55 ± 4%), and to a slightly lesser extent for the less active 1b (50 ± 1%) and 2a (45 ± 1%); however the extent of heme alkylation by these compounds was far lower than previously reported for the highly active trioxolanes 1a (86 ± 0.2%) and OZ277 (83 ± 2%). 30 Trioxepanes 3a and 3b mediated very little heme alkylation (25 ± 1% and 1 ± 0.4%), in agreement with their lack of antimalarial activity. The investigation of heme alkylation appears to give a more accurate prediction of antimalarial activity than investigation of iron-mediated reaction rates, suggesting that antimalarial activity is not merely dependant on peroxide bond cleavage, but also on the ability of reactive intermediates to alkylate heme or other proximal targets.…”
mentioning
confidence: 64%
“…Importantly, some Fe(II)-reactivity could still be detected for the next-generation ozonides. The cis-8′-phenyl-containing ozonides effectively and rapidly reacted with heme (with complete disappearance of the ozonide within minutes), with the extent of heme alkylation being comparable to that observed with the cis-8′-alkyl-containing compounds [e.g., 84 ± 1.5% heme alkylation for OZ439 and 83 ±1.5% for OZ277 (32), mean n = 3 ± SD]. Given that OZ439 and structurally related ozonides are potent antimalarials both in vitro against P. falciparum and in vivo against Plasmodium berghei (see below), these results strongly suggest that even low levels of Fe(II)-reactivity are sufficient to maintain antimalarial efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, ozonides that are essentially unreactive with Fe(II) in vitro are virtually devoid of antimalarial activity, although evidence of Fe (II)-reactivity on its own does not ensure antimalarial activity. We have also previously demonstrated that for a series of early synthetic ozonides, there is a good correlation between the extent of in vitro heme alkylation (which occurs subsequent to heme electron-transfer to the peroxide bond) and the in vitro IC 50 against P. falciparum, suggesting a potential link to antimalarial activity (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation